O neocalvinismo holandês e o movimento de cosmovisão cristã - Ramlow, Rodomar Ricardo (2012)
The purpose of this work is to present the authors and the main ideas which led to what became known as Dutch Neo-calvinism in the nineteenth century. From the development of ideas as the sovereignty of God, common grace, the cultural mandate, the criticism of theology and the Greek dichotomy and others, is that the Dutch men like Abraham Kuyper and Herman Dooyeweerd, had their lives marked as Christians who fought and lived for a Christianity that did not accept to be relegated within the church walls. Understanding Christianity as a comprehensive worldview from the Biblical ground-motive Creation-Fall-Redemption, the proponents of this reform movement influenced many Christian and thinkers worldwide. In recent years in Brazil it is also noted the role of people sympathetic to this movement and the emergence of publications on the subject of the Christian worldview. Markedly, a movement with claims of cultural reform and not merely ecclesiastical, initiatives are multiplying across the country. In addition to the authors that gave rise to the Dutch Neo-calvinism, this work also aims to focus on the emergence of the concept of Christian worldview and what the consequences are and the proposed inclusion of social and cultural proponents of the movement.